Lack of adequate counseling about pregnancy complications in patients with polycystic ovary syndrome: a cross-sectional survey study - Anne E. Kim, M.D; Iris T. Lee, M.D; Sasha Ottey, M.H.A; Anuja Dokras, M.D., M.H.C.I., Ph.D (Elsevier, 2024)
Objective: To assess the counseling experiences of patients with polycystic ovary syndrome (PCOS) related to obstetric complications and preconception management of comorbidities. Design: Cross-sectional survey study. Setting: Not applicable. Patient(s): Patients with PCOS with a history of or attempt at pregnancy. Intervention(s): Not applicable. Main Outcome Measure(s): Demographic characteristics, medical history, and counseling experiences. Result(s): Of the 302 respondents, 72.9% had a previous pregnancy, with 66.8% reporting complications during pregnancy. Of the entire cohort, 52.7% received preconception counseling on PCOS-related obstetric complications, and 41.5% were satisfied with their counseling experience. Five percent were counseled on related postpartum complications, and 43.4% received counseling about prepregnancy weight management, with the minority satisfied with their counseling. Among the respondents with existing comorbidities including hypertension, diabetes, and anxiety or depression, the minority received counseling on their preconception management. Although there were no racial disparities in the overall counseling of pregnancy complications, more black patients were counseled about preeclampsia, cesarean section, and preterm birth than white patients. Of the patients who had a single provider managing their PCOS care, 78.6% who saw a reproductive endocrinologist, 53.2% who saw a general gynecologist, and 35.0% who saw a primary care physician reported receiving counseling on related pregnancy complications. Conclusion(s): Despite the high prevalence of obstetric complications associated with PCOS, our study revealed inadequate patient counseling about both the antepartum and postpartum periods and preconception management of existing comorbidities. Our findings highlight the urgent need to increase provider education and patient awareness to optimize maternal and neonatal outcomes.